Predicting current and future global distribution of black rockfish (Sebastes schlegelii) under changing climate. (September 2021) - Chen, Yunlong; Shan, Xiujuan; Ovando, Daniel; Yang, Tao; Dai, Fangqun; Jin, Xianshi
Highlights: Species distribution models of black rockfish Sebastes schlegelii were developed . Ensemble model produced more accurate projections than any individual model. Out models predict that suitable habitat of S. schlegelii could decrease by up to 45% by the end of 2100. Climate-induced changes in spatial distributions should be considered for future management. Abstract: Changes in the marine environment, particularly climate change, can have large effects on the distribution patterns of various marine species, and alter the biodiversity, structure and functions of the affected ecosystems. Species distribution models (SDM) are tools often used to link species' ecological niches with their environment. We applied SDM to investigate the effects of five biologically relevant climatic variables from multiple databases, including bottom temperature, bottom salinity, current velocity, depth and primary productivity, on habitat suitability of Sebastes schlegelii in the marine waters of China, Korea and Japan. Nine individual SDM and an ensemble model were used to predict the current and future distribution of S. schlegelii under alternative climate change scenarios (Representative Concentration Pathways, RCP). Results indicated that the ensemble model produced more accurate projections than any individual model . Among the environmental variables investigated, bottom temperature was the most important in determining the range of S. schlegelii . Its current distribution demonstrated that suitable habitat for S. schlegelii was mostly concentrated in the Bohai Sea, coastal areas of the central and northern Yellow Sea, and in the Sea of Japan. Negative effects from climate change on the distribution patterns of S. schlegelii were predicted to lead to varying degrees of habitat reduction, with highest estimate of 45% occurring under RCP8.5 at the end of 2100. Our results illustrate the potential effects of climate change on the future distribution of S. schlegelii populations and can assist with implementing adaptive management measures of this species.